PENGARUH KEGIATAN EKSTRAKURIKULER DAN INTRAKURIKULER TERHADAP KARAKTER ISLAM SISWA SMP ISLAM TERPADU BUNAYYA BINA UL-UMMAH PADANGSIDIMPUN - Syafnan Lubis; Eni Sumanti Nasution; Hilda Khairani Nasution (FORUM PAEDAGOGIK, 2020)
This study aims to determine the effect of extracurricular activities on student character. This study was designed with a quantitative study with a sample size of 30 students with sampling using simple random sampling and simple linear regression analysis as a method of data analysis, the data collection instrument technique used was a questionnaire. The sampling method used was the random sampling technique by setting a sample of 30 students.The results showed that extracurricular activities were in the good category with 71% of the ideal score obtained. Meanwhile, the students' character was included in the very good category, with 83.8% of the ideal score and the extracurricular score of the students in the good category, namely 77.86%. The conclusions of this study are (1) There is a significant influence between extracurricular activities on Islamic character education at Bunayya Bina UL-UMMAH Padangsidimpuan Islamic Junior High School, (2) There is a significant influence between extracurricular activities on Islamic character in Islamic Junior High School. Integrated (IT) Bunayya Bina UL-UMMAH Padangsidimpuan the use of learning technology on student achievement at MTsN Padang Bolak, (3) There is a significant influence between extracurricular activities and extracurricular activities on Islamic character at the Integrated Islamic Junior High School (IT) Bunayya Bina UL-UMMAH Padangsidimpuan.Â Â